2017
DOI: 10.1097/igc.0000000000000883
|View full text |Cite
|
Sign up to set email alerts
|

Weekly Versus Triweekly Cisplatin-Based Chemotherapy Concurrent With Radiotherapy in the Treatment of Cervical Cancer: A Meta-Analysis

Abstract: Weekly cisplatin regimen had the similar therapeutic effect as the triweekly cisplatin regimen but with less hematologic toxicity. Therefore, we recommend the weekly cisplatin 30 to 40 mg/m chemoradiotherapy as the strong candidate for the optimal cisplatin dose and dosing schedule in the treatment of locally advanced cervical cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 20 publications
1
22
0
1
Order By: Relevance
“…95 The potential benefit of weekly versus 3-weekly cisplatin-based concurrent CTRT in LACC has also been investigated in 2 meta-analyses. 122,123 and a retrospective single-institution review. 124 The conclusions from these studies are blurred because of the inclusion of both singleagent cisplatin and mostly combination regimes in a triweekly arm and the inclusion of retrospective studies with adjuvant CTRT in patients postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…95 The potential benefit of weekly versus 3-weekly cisplatin-based concurrent CTRT in LACC has also been investigated in 2 meta-analyses. 122,123 and a retrospective single-institution review. 124 The conclusions from these studies are blurred because of the inclusion of both singleagent cisplatin and mostly combination regimes in a triweekly arm and the inclusion of retrospective studies with adjuvant CTRT in patients postoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…10 Although RTOG 90-01 used high-dose cisplatin 1 5-FU administered every 3 weeks, subsequent studies have shown that single-agent cisplatin administered weekly is less toxic and equally efficacious. [26][27][28] Virtually all patients in the cisplatin cohort of our study received weekly cisplatin, with a median of 5 cycles. Obtaining $5 cycles was required for benefit, with no difference in CSM seen in patients receiving 1 to 4 cycles versus no cisplatin.…”
Section: Discussionmentioning
confidence: 99%
“…A limitation of our study is that pharmacologic dose information is not available in the SEER-Medicare database. However, the most common dose of weekly cisplatin is 40 mg/m 2 , 26,27 suggesting that a total cisplatin dose of at least 200 mg/m 2 may be required for clinical benefit. This threshold is similar to that established in the GOG 109 study of patients treated with CRT in the adjuvant setting, in which at least 210 mg/m 2 (3 cycles of high-dose cisplatin) was required for benefit.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations